A blood pact: the significance and implications of eIF4E on lymphocytic leukemia - Venturi, V; Mašek, Tomáš; Pospíšek, Martin (Physiological research, 2018)
Elevated levels of eukaryotic initiation factor 4E (eIF4E) are implicated in neoplasia, with cumulative evidence pointing to its role in the etiopathogenesis of hematological diseases. As a node of convergence for several oncogenic signaling pathways, eIF4E has attracted a great deal of interest from biologists and clinicians whose efforts have been targeting this translation factor and its biological circuits in the battle against leukemia. The role of eIF4E in myeloid leukemia has been ascertained and drugs targeting its functions have found their place in clinical trials. Little is known, however, about the pertinence of eIF4E to the biology of lymphocytic leukemia and a paucity of literature is available in this regard that prospectively evaluates the topic to guide practice in hematological cancer. A comprehensive analysis on the significance of eIF4E translation factor in the clinical picture of leukemia arises, therefore, as a compelling need. This review presents aspects of eIF4E involvement in the realm of the lymphoblastic leukemia status; translational control of immunological function via eIF4E and the state-of-the-art in drugs will also be outlined.
Keywords: antitumorózní látky; Humans; Eukaryotic Initiation Factor-4E; lymfoidní leukemie; lidé; Leukemia, Lymphoid; regulace genové exprese u leukemie; Antineoplastic Agents; Gene Expression Regulation, Leukemic; eukaryotický iniciační faktor 4E